A thermal behaviour study of natural fiber-reinforced polymer composite/honeycomb core sandwich panels - Muhammad Zulkarnain; Azman, Mohamad Izmul Farees; Insdrawaty, Mohamad Irfan; Azmi, Muhamad Izwan Aiman; Zainol, Mohd Faez (Penerbit UTM Press, 2024)
The unique honeycomb structure has provided good modulus with a lightweight material, especially in aerospace and vehicle applications. Realizing that the thermal analysis of natural fiber honeycomb sandwiches was still lacking in observation, the research needs to investigate thermal transfer characteristics to promote engineering demand. The objective of this research was to investigate honeycomb sandwiches' thermal behaviour by implementing local natural fibers of coconut, oil palm, and sugar cane for sheet plate structure through experimental and numerical analysis. The natural fiber was varied by weight content with the ratio of composite given in a range of 0%wt.-8%wt. The results have demonstrated that the face sheet plate was paramount part to absorb thermal flow. The study displayed the low thermal conductivity of the face sheet will counter significantly the heat transfer of the honeycomb structure. The experimental investigation found that the coconut fiber successfully performs as an insulator in a honeycomb sandwich which reached 6.78 W.m-1K-1 of thermal conductivity which was an 85.86% improvement as an insulator. While palm oil and sugar cane presented at 11.12 W.m-1K-1 and 10.59 W.m-1K-1, it was slightly higher compared to the coconut. In the numerical investigation, fiber distribution development was successfully performed in a honeycomb sandwich sheet plate composite. The thermal conductivity showed a difference from the experimental, where the higher thermal resistance was shown by palm oil and sugar cane at 8.22 W.m-1K-1 and 8.16 W.m-1K-1, respectively. This difference was much influenced by the morphology factor in fiber orientation of the experimental study.